Model-Based Meta-Analysis on the Efficacy of Biologics and Small Targeted Molecules for Crohn’s Disease - Yu, Boran; Zhao, Libo; Jin, Siyao; He, Huan; Zhang, Jing; Wang, Xiaoling (Frontiers in Immunology, 2022)
Information on the comparative drug efficacy is of great importance for drug development as well as clinical practice. Up to now, the relative efficacy of biologics and small targeted molecules for Crohn's disease (CD) remains unclear. The object of this study was to quantify the relative efficacy of investigational and approved biological treatments for CD measured in Crohn's Disease Activity Index (CDAI), Inflammatory Bowel Disease Questionnaire (IBDQ), and C-reactive protein (CRP). The analysis dataset was composed of summary-level data from 46 trials, containing 12846 patients, with treatment of 24 drugs. Six mathematical models with nonparametric placebo estimations were developed to describe the time-course and dose-response of six efficacy measures. The effects of covariate were further evaluated. Time-response relationships were found in outcomes measured in CDAI. Patient’s age, disease duration, baseline CDAI and CRP showed impact on the efficacy. Model simulations were performed to compare the efficacies across different drugs. Important differences between and within drug classes were identified. TNF-a inhibitor, IL-23 inhibitor, and integrin-a4 inhibitor were detected to be the most effective biologic agents. These findings have important implications for clinical practice in CD.